Avaliação da atividade e do mecanismo de ação anti-inflamatório e imunoregulador do extrato hidroetanólico das folhas de Echinodorus scaber Rataj e vitexina - Rosa, Suellen Iara Guirra (2015)
The leaves of Echinodorus scaber (Alismataceae), known as a leather hat, are used in folk medicine to treat inflammation, allergies, kidney infections, rheumatism and respiratory diseases. Preliminary phytochemical analyzes from the hydroethanolic extract of Echinodorus scaber leaves (EHEs) revealed the presence of different secondary metabolites, among them the presence of flavonoid vitexin as one of its main components. This work evaluates the mechanism of cellular and molecular anti-inflammatory action of EHEs and vitexin. The anti-inflammatory and immunoregulatory activity of EHEs was evaluated in the ovalbumin-induced allergic asthma model (OVA) in Swiss mice, submitted to histopathological analysis of the lung on the 25th day. The effect of EHEs (1, 5 and 30 mg / kg v.o) on the concentration of TH2 cytokines (IL-4, IL-5 and IL-13) in BAL and serum immunoglobulin (Ig) E were assessed by ELISA. The anti-inflammatory activity of vitexin was evaluated in vivo and in vitro. In vivo models include evaluation of the leukocyte migration to the peritoneal cavity induced by zymosan, carrageenan, fMLP and LPS and the effects on the levels of cytokines (TNF-α, IL-1β and IL-10) and of NO, which were evaluated in a model of peritonitis induced by LPS. In vitro analyzes include the viability of RAW 264.7 versus Vitexin macrophages by the Alamar Blue test, evaluation of the effect on TNF-α, IL1β, IL-10, NO and PGE2 concentrations in the supernatant by ELISA, and on the MAPKs pp38, p-ERK1 / 2 and p-JNK by western blotting on LPS-activated RAW 264.7 cells. At all doses tested, EHEs reduced the total number of leukocytes, eosinophils, neutrophils and mononuclear cells in BAL. It also reduced IL-4, IL-5 and IL-13 concentrations in BAL as well as serum IgE levels. Histopathological analyzes revealed that treatment with 30 mg / kg of EHEs caused reduction of edema and mucus. Vitexin at all doses (5, 15 and 30 mg / kg) was effective in reducing leukocyte migration in vivo, particularly neutrophils in the peritoneal lavage, regardless of the inflammatory stimulus used. It also reduced the release of TNF-α, IL-1β and NO into the peritoneal cavity of LPS-challenged mice. Vitexin at all doses (5, 15 and 30 mg / kg) was effective in reducing leukocyte migration in vivo, particularly neutrophils in the peritoneal lavage, regardless of the inflammatory stimulus used. It also reduced the release of TNF-α, IL-1β and NO into the peritoneal cavity of LPSchallenged mice. Vitexin showed low cytotoxicity (IC 50> 200 μg / mL) and was able to reduce the release of TNF-α, IL-1β, NO, PGE2 and increase IL-10 release in LPSstimulated RAW 264.7 cells. Vitexin reduced the expression of p-p38, p-ERK1 / 2 and pJNK MAPKs in LPS-induced cells. The results show that EHEs and vitexin have a mechanism of multi-target anti-inflammatory action and that vitexin in synergy with other metabolites respond, at least in part, to the anti-inflammatory action of EHEs.